Characterization and evaluation for wound healing of chitosan extracted from the exoskeleton of freshwater crab Potamonautes niloticus - Mohamed Abdelnaser Amer, Enas M.H. Attia (Journal of Applied Pharmaceutical Science, 2020)
The freshwater crab Potamonautes niloticus (Potamonautidae: Decapoda: Crustacea) is common in River Nile and its tributaries but has no commercial value as edible crab for human beings. Therefore, the present study aims to evaluate the role of chitosan extracted from its exoskeleton for wound healing process as a medical application. The structure of chitosan has been physically investigated by using fourier transformer infrared spectroscopy to reveal the vibrational frequencies of different structural functional groups, such as primary amine groups, hydroxyl groups and amide groups. The efficiency of the extracted chitosan was assessed by morphological and histological examination of wound healing in albino rats. Sections of isolated wounds were stained with hematoxylin and eosin to evaluate the histological changes during the wound healing process. Chitosan was yielded 30.64% from the crab shells and the results of wound healing assessments showed that the chitosan treated group (Ch 1%) was more efficient and faster than other groups (Ch 2, 3%) versus control groups. Also, the total leucocyte counts showed shortened inflammatory phase in chitosan-treated groups. The present results showed the efficiency of extracted chitosan in wound healing process and can be used in medical applications.
Keywords: Re-epithelization, inflammatory phase, chitin, crustacean shells.